Antibacterial and antifogging sheet, manufacturing method thereof and antibacterial and antifogging glasses containing antibacterial and antifogging sheet

By using a dual-ion polymer aqueous solution for plasma treatment, an antibacterial and anti-fog coating was formed, which solved the problems of poor anti-fog effect and insufficient adhesion in the prior art, and achieved efficient anti-frost effect and good durability. .

CN119490682APending Publication Date: 2025-02-21TAIWAN SOKOU INDS KOFUN YUUGENKOUSHI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311044464.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing hydrophobic smoothing layer has poor anti-fog effect, while the hydrophilic smoothing layer has poor adhesion to the substrate and is prone to fall off.

Method used

Plasma treatment is performed using a aqueous solution of two-ion polymers to make the two-ion polymers have free radicals, thereby forming an antibacterial and anti-fog coating on the sheet. The coating has high hydrophilicity, can effectively prevent mist formation, and has good adhesion and durability.

Benefits of technology

The anti-fog and anti-bacterial properties of anti-bacterial sheets are achieved, and at the same time they have good durability, and can maintain anti-fog and anti-bacterial effects after multiple uses and friction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490682A_ABST
    Figure CN119490682A_ABST
Patent Text Reader

Abstract

The invention relates to an antibacterial and antifogging sheet, a manufacturing method thereof and antibacterial and antifogging glasses containing the antibacterial and antifogging sheet. The specific dual-ion polymer used by the antibacterial and antifogging sheet has high hydrophilicity and can be dissolved in water, and the dual-ion polymer has free radicals through water plasma treatment, so that an antibacterial and antifogging coating can be formed on the sheet. The obtained antibacterial and antifogging sheet has antibacterial property, antifogging property and excellent durability, and can be applied to manufacturing antibacterial and antifogging glasses.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an antibacterial anti-fog sheet, in particular to an antibacterial anti-fog sheet containing a double ion polymer, a manufacturing method thereof and antibacterial anti-fog glasses containing the same. Background Art

[0002] Wearing glasses is one of the means to correct vision problems such as myopia, hyperopia, astigmatism, presbyopia and / or strabismus. Glasses include glass, resin or polycarbonate as a substrate, and an optical layer is coated on the substrate to achieve anti-reflection, anti-ultraviolet, anti-blue light and other effects. The optical layer usually also includes a smooth layer to make the glasses easier to clean and less likely to be stained.

[0003] However, although the existing hydrophobic smooth layer can achieve the anti-fogging effect by making water vapor form water droplets and slide down without staying due to the low surface tension of the hydrophobic smooth layer, the anti-fogging effect of the hydrophobic smooth layer is not good after actual testing. Although the existing hydrophilic smooth layer can achieve the anti-fogging effect by making water vapor form a water film due to the high surface tension of the hydrophobic smooth layer, thereby preventing the water droplets from scattering the incident light, the hydrophilic material has poor adhesion to the substrate and is easily detached after friction and / or washing.

[0004] Therefore, there is an urgent need for a method for manufacturing an antibacterial anti-fog sheet to solve the above problems. Summary of the invention

[0005] Therefore, one aspect of the present invention is to provide a method for manufacturing an antibacterial anti-fog sheet, in which the diionic polymer used has high hydrophilicity and is therefore soluble in water. The diionic polymer is treated with water plasma to have free radicals, which helps to form an antibacterial and anti-fog coating on the sheet that has antibacterial and anti-fog properties and good durability.

[0006] Another aspect of the present invention is to provide an antibacterial anti-fog sheet, which is made using the above-mentioned manufacturing method.

[0007] Another aspect of the present invention is to provide an antibacterial anti-fog glasses comprising the antibacterial anti-fog sheet.

[0008] According to the above aspect of the present invention, a method for manufacturing an antibacterial anti-fog sheet is provided. First, a dual-ion polymer aqueous solution is provided, wherein the dual-ion polymer aqueous solution comprises a dual-ion polymer and water. The dual-ion polymer comprises the copolymer described in Formula 1.

[0009]

[0010] R 1 is a thioether containing at least two acrylate groups. 2 and R 3 is a hydrogen atom or a methyl group.4 are COOR' and CONR", and R' and R" are betaine, sulfobetaine or carboxybetaine.

[0011] Next, the dual ion polymer aqueous solution is ionized by gas plasma to obtain a plasma activated dual ion polymer aqueous solution. Then, the sheet is immersed in the plasma activated dual ion polymer aqueous solution to obtain an antibacterial anti-fog sheet.

[0012] In one embodiment of the present invention, the sheet is subjected to plasma surface treatment before being immersed in the plasma activated dual ion polymer aqueous solution.

[0013] In one embodiment of the present invention, the sheet includes a substrate and at least two anti-reflective coating (AR) layers, wherein the substrate is disposed between the at least two anti-reflective coating layers.

[0014] In one embodiment of the present invention, based on the usage of the dual-ion polymer aqueous solution being 100 weight percent, the usage of the dual-ion polymer is 30 weight percent to 50 weight percent.

[0015] In one embodiment of the present invention, the ionization treatment allows the diionic polymer to have at least one free radical.

[0016] In one embodiment of the present invention, the antibacterial anti-fog sheet has at least one antibacterial anti-fog layer, and the thickness of at least the antibacterial anti-fog layer is 0.5 μm to 50 μm.

[0017] In one embodiment of the present invention, the ionization treatment is performed at 5° C. to 50° C. and 0.5 atmosphere to 1.5 atmosphere for 5 minutes to 120 minutes.

[0018] In one embodiment of the present invention, the sheet is immersed in the plasma activated dual ion polymer aqueous solution for 5 minutes to 120 minutes.

[0019] According to the above aspect of the present invention, an antibacterial anti-fog sheet is provided, which is made by using the above manufacturing method.

[0020] According to another aspect of the present invention, an antibacterial anti-fog eyeglasses is provided, which comprises the antibacterial anti-fog sheet.

[0021] The antibacterial anti-fog sheet, the manufacturing method thereof and the antibacterial anti-fog glasses containing the same are applied. The specific diionic polymer used in the antibacterial anti-fog sheet has high hydrophilicity and can be dissolved in water. After being treated with water plasma, the diionic polymer has free radicals, which helps to form an antibacterial anti-fog coating on the sheet. The prepared antibacterial anti-fog sheet has antibacterial and anti-fog properties and good durability, and can be used to manufacture antibacterial anti-fog glasses. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to make the above and other objects, features, advantages and embodiments of the present invention more clearly understood, the detailed description of the attached drawings is as follows:

[0023] Figure 1 FIG. 4 is a flow chart illustrating a method for manufacturing an antibacterial anti-fog sheet according to some embodiments of the present invention. DETAILED DESCRIPTION

[0024] As mentioned above, the present invention provides an antibacterial anti-fog sheet, a method for manufacturing the same, and antibacterial anti-fog glasses containing the same. The antibacterial anti-fog sheet is made using a specific diionic polymer, wherein the diionic polymer has high hydrophilicity and is soluble in water, and an antibacterial anti-fog coating is formed on the sheet through water plasma treatment, so that the antibacterial anti-fog sheet has antibacterial and anti-fog properties, and has good durability.

[0025] The "antibacterial property" described herein refers to the property that pathogens and / or their vectors are difficult to non-specifically adsorb on the surface of the antibacterial anti-fog sheet. In some embodiments, pathogens may include but are not limited to fungi, bacteria and / or viruses. In some embodiments, the vectors of pathogens may include but are not limited to dust, droplets and / or aerosols carrying pathogens.

[0026] The antibacterial property can be evaluated by the relative bacterial percentage or relative antibacterial rate obtained in the antibacterial test. In some embodiments, the antibacterial test is to place the antibacterial anti-fog sheet in a bacterial solution and culture it at 35°C to 40°C for 20 to 30 hours, and then calculate the amount of bacteria on the surface of the sheet, wherein the bacteria can be, for example, Escherichia coli or Staphylococcus aureus.

[0027] The above relative bacterial percentage is the amount of bacteria on the surface of the antibacterial anti-fog sheet (i.e., N 1 ) compared to the amount of bacteria on the surface of the sheet (not treated with dual ion polymer water plasma) (i.e., N 0 ) percentage [i.e., (N 1 / N 0 )×100%]. The relative antibacterial rate is the difference between 100% and the relative bacterial percentage [i.e., 100%-(N 1 / N 0 )×100%], which is equivalent to the amount of bacteria on the surface of the sheet (i.e., N 0 ) and the amount of bacteria on the surface of the antibacterial anti-fog sheet (i.e., N 1 ) relative to the amount of bacteria on the surface of the sheet (i.e., N 0 ) percentage [i.e., (N 0 -N 1 ) / N 0× 100%]. In some embodiments, the antibacterial property is a relative bacteria percentage of less than 20%, which is equivalent to a relative antibacterial rate of greater than 80%.

[0028] The "anti-fog property" described herein refers to the fact that after water vapor condenses on the antibacterial anti-fog sheet, no fog that affects the line of sight is formed. The anti-fog property can be evaluated by an anti-fog test, which is to place the antibacterial anti-fog sheet on warm water for a period of time and then visually evaluate the light transmittance and / or water droplet adhesion of the antibacterial anti-fog sheet. In a specific example, when evaluating the anti-fog property, the temperature of the warm water can be, for example, 45°C to 55°C, and the standing time can be 30 seconds to 90 seconds.

[0029] The "durability" described herein means that after multiple uses, the antibacterial anti-fog sheet still has antibacterial and / or anti-fog properties, and the weight loss rate is small. The above-mentioned multiple use scenarios include multiple washings, long-term placement or multiple frictions. In some embodiments, durability can be evaluated after multiple washings. The antibacterial and / or anti-fog properties of the antibacterial anti-fog sheet are evaluated. In some specific examples, multiple washings are to immerse the antibacterial anti-fog sheet in water and then take it out, and repeat this action 40 to 60 times.

[0030] In some embodiments, the durability can be tested by exposing the antibacterial anti-fog sheet to ultraviolet light to simulate the change over time, and then evaluating the anti-fog and / or antibacterial properties of the antibacterial anti-fog sheet. In some specific examples, the antibacterial anti-fog sheet is exposed to ultraviolet light for 8 to 14 hours, and then placed in the dark for 8 to 14 hours to simulate the change of the antibacterial anti-fog sheet after being placed for 3 years. The irradiance of the ultraviolet light can be, for example, 0.65 W / m 2 / nm to 0.75W / m 2 / nm, the wavelength of the ultraviolet light may be, for example, 280nm to 400nm, such as 320nm to 360nm, or 340nm, and the temperature is 50℃ to 70℃, such as 60℃.

[0031] In some embodiments, durability can be evaluated by a steel wool test, which is to evaluate the weight loss rate of the antibacterial anti-fog sheet after rubbing the antibacterial anti-fog sheet with a weighted steel wool, wherein the weight loss rate is the weight difference between the antibacterial anti-fog sheet before and after the steel wool rubbing and the weight of the antibacterial anti-fog sheet before the steel wool rubbing. The steel wool test is carried out with different weights and the number of back and forth frictions to compare the durability of the antibacterial anti-fog sheet for multiple frictions. In some specific examples, the durability of the antibacterial anti-fog sheet of the present invention is that the weight loss rate of the antibacterial anti-fog sheet is less than 1 weight percentage after the antibacterial anti-fog sheet is rubbed back and forth 40 to 60 times with steel wool with a weight greater than 200g to 400g.

[0032] For the manufacturing method of antibacterial anti-fog sheet, please refer to Figure 1, which depicts a flow chart of a method 100 for manufacturing an antibacterial anti-fog sheet according to some embodiments of the present invention. Figure 1 As shown in step 110, a diionic polymer aqueous solution is provided, which includes diionic polymer and water. In some embodiments, based on the usage of the diionic polymer aqueous solution being 100 weight percent, the usage of the diionic polymer is 30 weight percent (wt %) to 50 weight percent.

[0033] In some embodiments, the diionic polymer comprises the copolymer described in Formula 1.

[0034]

[0035] R 1 is a thioether comprising at least two acrylate groups. 1 Yes (CH 2 ) x S(CH 2 ) y CH(COOC 2 H 3 ) 2 or (CH 2 ) x S(CH 2 ) y CH(COOC 2 H 3 )CH 2 (COOC 2 H 3 ), wherein x is an integer from 0 to 5, and y is an integer from 0 to 5. In some embodiments, R 1 It is SCH(COOC 2 H 3 ) 2 In other embodiments, R 1 Yes (CH 2 )S(CH 2 ) 4 CH(COOC 2 H 3 )CH 2 (COOC 2 H 3 ). Due to R 1 With at least two acrylate groups, the diionic polymer can be hydrophilic, thereby preparing a diionic polymer aqueous solution.

[0036] R 2 and R 3 is a hydrogen atom or a methyl group. 4are COOR' and CONR", and R' and R" are betaine, sulfobetaine, carboxybetaine or derivatives thereof, so that the antibacterial and antifog sheet obtained has antibacterial and antifog properties. In some specific examples, the diionic polymer includes a copolymer as shown in Formula 2, Formula 3 or Formula 4.

[0037]

[0038] In some embodiments, the average molecular weight of the diionic polymer may be, for example, 5000 to 10000, so that the diionic polymer can be grafted onto the surface of the substrate more evenly, and the density of the formed antibacterial antifogging layer is sufficient to form a biologically inert surface with antibacterial properties.

[0039] The diionic polymer has high hydrophilicity. In some embodiments, the water contact angle of the substrate not treated with water plasma is 50° to 80°, but after the substrate is treated with water plasma of the diionic polymer, the water contact angle is 10° to 40°.

[0040] Next, the water plasma treatment shown in step 120 is performed. In detail, step 120 includes step 122 and step 124, wherein step 122 is to use gas plasma to ionize the diionic polymer aqueous solution to obtain a plasma-activated diionic polymer aqueous solution. Step 124 is to immerse the sheet in the plasma-activated diionic polymer aqueous solution so that the diionic polymer in the plasma-activated diionic polymer aqueous solution is grafted on the surface of the substrate, thereby forming an antibacterial antifog coating on both surfaces of the sheet, thereby obtaining an antibacterial antifog sheet. In some embodiments, the immersion time may be, for example, 5 minutes to 120 minutes, such as: 10 minutes to 60 minutes, so that the diionic polymer can be appropriately entangled, and the antibacterial antifog coating formed may have better antibacterial properties. In some embodiments, the thickness of the antibacterial antifog coating may be, for example, 0.5 μm to 50 μm.

[0041] It is worth noting that the gas plasma in step 122 can be obtained by, for example, treating air or oxygen with plasma. The plasma treatment can be performed by conventional methods, such as low-temperature vacuum plasma or low-temperature atmospheric pressure plasma. In some specific examples, the low-temperature atmospheric pressure plasma can include, but is not limited to, jet plasma, dielectric layer discharge, or corona discharge.

[0042] The ionization treatment may be, for example, to pass gas plasma into a tank containing a dual-ion polymer aqueous solution, so that the dual-ion polymer in the dual-ion polymer aqueous solution has free radicals to enhance its reactivity, thereby facilitating the formation of an antibacterial and anti-fog coating on the surface of the sheet.

[0043] In some embodiments, the ionization treatment can be carried out at room temperature and normal pressure, wherein the room temperature can be, for example, 5°C to 50°C, or 10°C to 45°C, or 15°C to 35°C, or 20°C to 30°C. In some embodiments, the normal pressure can be, for example, 0.5 atmospheres (atm) to 1.5 atmospheres, or 0.8 atmospheres to 1.2 atmospheres. In some embodiments, the time of the ionization treatment can be, for example, 5 minutes to 120 minutes, such as: 10 minutes to 60 minutes, or 20 minutes to 60 minutes.

[0044] In some embodiments, the sheet may include a substrate and an anti-reflective coating (AR) layer, wherein the AR layer is disposed on the corresponding two side surfaces of the substrate, that is, the substrate is disposed between the AR layers. Therefore, the antibacterial anti-fog coating formed above is formed on the surface of the AR layer.

[0045] The sheet material may be a commercially available corrective lens, such as a lens for myopia, strabismus, astigmatism, hyperopia, hyperopia, and presbyopia. In some embodiments, one of the surfaces of the sheet material may be a plane, a spherical surface, or an aspherical surface, wherein the aspherical surface is a curved surface formed by a spherical surface with multiple curvature radii.

[0046] The materials of the substrate and the anti-reflection layer of the sheet can be existing materials. In some embodiments, the substrate can be, for example, glass, polycarbonate (PC), triacetate cellulose film (TCF), nylon, poly(allyl carbonate) diglycol ester (CR-39), polymethylmethacrylate (PMMA), polyethyleneterephthalate (PET), or polypropylene (PP).

[0047] In some embodiments, the material of the anti-reflective coating (AR) layer may be, for example, titanium dioxide, silicon dioxide, zirconium dioxide or magnesium fluoride. In some embodiments, the anti-reflective layer may be a multi-layer layer to reduce the reflectivity of incident light.

[0048] In some embodiments, before dipping the sheet in the plasma activated dual ion polymer aqueous solution, the sheet is subjected to plasma surface treatment to enhance the reactivity of the sheet surface. The plasma surface treatment includes using conventional plasma treatment. Conventional plasma treatment has been listed above and will not be described in detail here.

[0049] The antibacterial anti-fog sheet prepared by the above method has been confirmed to have anti-fog and antibacterial properties through experiments. 1 The sulfide of the diionic polymer contains only one acrylate group, and the diionic polymer of the present invention has R 1 The thioether contains at least two acrylate groups, and the formed antibacterial anti-fog coating has better adhesion to the surface of the sheet, so that the prepared antibacterial anti-fog sheet still has anti-fog and / or antibacterial properties after multiple washings and / or long-term use, and has a low weight loss rate after multiple frictions and good durability.

[0050] It should be noted that the existing plasma treatment (such as plasma-assisted chemical vapor deposition process) requires first heating the material to be deposited on the surface of the substrate to 40°C to 80°C to form a gaseous material, and then using a carrier gas to allow the gaseous material to flow into the cavity and be deposited and grafted on the surface of the substrate. However, diionic polymers are difficult to vaporize, so they cannot be treated with existing plasma (such as plasma-assisted chemical vapor deposition process). However, the diionic polymers used in the method for manufacturing the antibacterial anti-fog sheet of the present invention have high hydrophilicity and reactive functional groups, so the diionic polymers can be grafted on the surface of the substrate through water plasma treatment, thereby improving the durability of the antibacterial anti-fog layer obtained.

[0051] Several embodiments are used below to illustrate the application of the present invention, but they are not used to limit the present invention. Those skilled in the art of the present invention can make various changes and modifications without departing from the spirit and scope of the present invention.

[0052] Preparation Example 1

[0053] First, a monomer 1 as shown in Formula 5 is prepared, which is prepared by polymerization of allyl mercaptan and glycidol in ethyl acetate under the catalysis of triethylamine (TEA).

[0054]

[0055] Next, a monomer 2 represented by Formula 6 was prepared, which was prepared by reacting 2-(2-dimethylamino) methacrylate with 1,3-propane sultone in an acetone solvent by betaining for 24 hours.

[0056]

[0057] Then, in a nitrogen environment, using ethanol as a solvent, copper bromide / bipyridine (CuBr / 2,2'-bipyridine; CuBr / bpy) as a catalyst, and methyl 2-bromopropionate (MBrP) as a polymerization initiator, monomer 1 and monomer 2 are subjected to atom transfer radical polymerization to form polymer 1 as shown in Formula 7.

[0058]

[0059] Next, triethylamine was used to catalyze the reaction of polymer 1 and propylvinyl chloride to obtain a diionic polymer (as shown in Formula 2). Then, the diionic polymer was prepared into a 40 weight percent diionic polymer aqueous solution. Air plasma was prepared using low-temperature atmospheric pressure plasma, and then the air plasma was passed into the diionic polymer aqueous solution at 25° C. and 1 atmosphere to perform ionization treatment for 15 minutes, thereby obtaining a plasma-activated diionic polymer aqueous solution.

[0060] The lens is subjected to plasma surface treatment for 10 to 60 minutes by low-temperature atmospheric pressure plasma. The lens is a commercially available corrective lens, comprising a substrate and an anti-reflective layer, wherein the substrate is poly(allyl diglycol carbonate) (CR-39), and the anti-reflective layer is silicon dioxide. The plasma-surface-treated lens is immersed in a plasma-activated diionic polymer aqueous solution for 20 to 60 minutes to form a coating on the surface of the lens, thereby preparing the sheet of Preparation Example 1. It is worth noting that although Preparation Example 1 only uses the diionic polymer comprising the polymer shown in Formula 2 as an example, the sheet is prepared using the diionic polymer comprising the polymer shown in Formula 3 and Formula 4, and the results obtained by the evaluation method should be the same as those of Preparation Example 1, which will not be repeated here.

[0061] Preparation of Comparative Example 1

[0062] The sheet of Preparation Comparative Example 1 is the lens of Preparation Example 1, but is not immersed in the plasma-activated dual-ion polymer aqueous solution.

[0063] Preparation of Comparative Example 2

[0064] The sheet prepared in Comparative Example 2 is the same as that prepared in Example 1, except that the diionic polymer prepared in Comparative Example 2 comprises a polymer 2 as described in Formula 8, which is prepared using methanol allyl sulfide as a monomer 1, wherein the monomer 1 has only one acrylate group.

[0065]

[0066] Preparation of Comparative Example 3

[0067] The sheet material of Comparative Example 3 is prepared in the same manner as that of Preparation Example 1, except that the coating of Comparative Example 3 is formed by immersing the sheet material in a coating composition and drying it at 120° C. for 30 minutes. The coating composition comprises a polymer 3 represented by Formula 9 and vinyltrimethoxysilane, which are polymerized at 60° C., and p in Formula 9 is 14.

[0068]

[0069] Evaluation methods and results

[0070] 1. Anti-fog test

[0071] The anti-fogging properties of the sheets of Preparation Example 1 and Preparation Comparative Examples 1 to Preparation Comparative Examples 3 were evaluated by an anti-fogging test. The anti-fogging test was performed by placing a beaker of 50°C warm water on a white-bottomed patterned paper, placing the sheet on the beaker for 1 minute, and then observing the clarity of the pattern on the paper through the sheet. The results are recorded in Table 1, where "0" indicates a clear pattern and "╳" indicates a blurred pattern.

[0072] 2. Antibacterial Test

[0073] The antibacterial property of the sheet of Preparation Example 1 was evaluated by antibacterial test. First, the front and back sides of the sheet of Preparation Example 1 were irradiated with ultraviolet light for 5 minutes each to sterilize the sheet of Preparation Example 1, wherein the front side of the sheet of Preparation Example 1 refers to the side where the number of bacteria on the surface is sampled in subsequent experiments. Then, the sheet of Preparation Example 1 was placed face up in a culture dish containing bacterial solution, and the bacteria were cultured at 37°C for 24 hours, so that the bacterial concentration in the bacterial solution was 2.5×10 5 Colony-forming unit (CFU) / mL to 10.0×10 5 CFU / mL.

[0074] Then, the sheet of Preparation Example 1 was taken out from the culture dish, and after removing the liquid visible to the naked eye, the sheet of Preparation Example 1 was washed, and the liquid on the surface of the sheet of Preparation Example 1 was drained. The washing method was to soak the sheet in phosphate buffered saline (PBS) for 5 minutes, and then soak the sheet in fresh PBS. Next, 10 mL of lecithin and 80% soybean casein digestion medium (soybean casein digestlecithin polysorbate 80 medium, SCDLP) was used to rinse the front of the test piece to obtain a rinse solution. 1 mL of the rinse solution was applied to the medium and incubated at 37°C for 24 hours. The number of colonies in the medium (i.e., N 1The number of colonies (i.e., N) of Comparative Example 1 was obtained by the above method. 0 ).

[0075] Calculate the number of colonies (i.e., N) of the culture medium of Preparation Example 1 1 ) and the number of colonies in the culture medium of Comparative Example 1 (i.e., N 0 ) percentage [i.e., (N 1 / N 0 )×100%] to obtain the relative bacterial percentage of Preparation Example 1. Then, the difference between 100% and the relative bacterial percentage of Preparation Example 1 was calculated [i.e., 100%-(N 1 / N 0 )×100%] to obtain the relative antibacterial rate.

[0076] Next, the relative bacterial percentages of Preparation Comparative Example 2 and Preparation Comparative Example 3 relative to Preparation Comparative Example 1 were obtained in the same manner. It is additionally noted that the above-mentioned bacteria are Escherichia coli, and the culture medium is LB culture agar. The results are recorded in Table 1, where "0" indicates that the relative antibacterial rate is ≥80%, and "╳" indicates that the relative antibacterial rate is <80%.

[0077] 3. Anti-fogging properties of the sheet after multiple washings

[0078] The sheets of Preparation Example 1, Preparation Comparative Examples 1 to Preparation Comparative Examples 3 were immersed in water and then taken out, and the process was repeated 50 times. The above-mentioned method for evaluating anti-fogging properties was then used to evaluate whether the sheets had anti-fogging properties after multiple water washings. The results are recorded in Table 1, where "0" indicates a clear pattern and "╳" indicates a blurred pattern.

[0079] 4. Steel wool test

[0080] The weight loss rate of the sheet after multiple frictions was evaluated by the steel wool test. First, the first steel wool test was to measure the weight of the sheet of Preparation Example 1, and then rub the surface of the sheet of Preparation Example 1 20 times with steel wool weighing 200 g, and then measure the weight of the sheet of Preparation Example 1. The difference between the weight of the sheet of Preparation Example 1 before and after friction and the percentage of the weight before friction treatment were calculated to obtain the weight loss rate.

[0081] The second steel wool test is to first measure the weight of the sheet of Preparation Example 1, and then rub the surface of the sheet of Preparation Example 1 with steel wool weighing 400g back and forth 60 times, and then measure the weight of the sheet of Preparation Example 1. The difference between the weight of the sheet of Preparation Example 1 before and after the friction treatment and the percentage of the weight before the friction treatment are calculated to obtain the weight loss rate. The weight loss rates of the sheets of Preparation Comparative Examples 1 to Preparation Comparative Examples 3 are evaluated in the same way. The results are recorded in Table 1, where "0" indicates a weight loss rate of <1%, and "╳" indicates a weight loss rate of ≥1%.

[0082] Table 1

[0083]

[0084] N / A means not assessed, not applicable

[0085] As shown in Table 1, the results of the anti-fog test and the antibacterial test show that the sheet of Preparation Example 1 has antibacterial and anti-fog properties. Secondly, the sheet of Preparation Example 1 still has anti-fog properties after multiple water washings and long-term use, and the weight loss rate after multiple frictions is low, indicating good durability.

[0086] The sheet of Preparation Comparative Example 1 has no coating on its surface and has no anti-fog property. It also has no anti-fog property after multiple water washings and long-term storage, and has a high weight loss rate after multiple frictions. The coating of the sheet of Preparation Comparative Example 2 has fewer acrylate groups, and the adhesion of the coating is poor. Although it has antibacterial and anti-fog properties, it does not have anti-fog properties after multiple water washings or long-term use. It has a high weight loss rate after multiple frictions and poor durability. The coating of the sheet of Preparation Comparative Example 3 is formed by coating, and has antibacterial and anti-fog properties. However, judging from the anti-fog property after multiple water washings or long-term use, and the weight loss rate of the second steel wool test, the durability of the sheet of Preparation Comparative Example 3 is worse than that of Preparation Example 1.

[0087] It can be seen from the above embodiments that the antibacterial anti-fog sheet material, the manufacturing method thereof and the antibacterial anti-fog glasses containing the same of the present invention have the advantages of using specific diionic polymers. Due to the high hydrophilicity of the diionic polymers, they can be dissolved in water, and through water plasma treatment, the diionic polymers have free radicals, which helps to form an antibacterial anti-fog coating on the sheet material. The obtained antibacterial anti-fog sheet material has anti-fog and / or antibacterial properties and good durability, and can be used to manufacture antibacterial anti-fog glasses.

[0088] Although the present invention has been disclosed as above with several specific embodiments, various modifications, changes and substitutions may be made to the aforementioned disclosure, and it should be understood that in some cases, certain features of the embodiments of the present invention will be adopted but other features will not be used accordingly without departing from the spirit and scope of the present invention. Therefore, the spirit and scope of the claims of the present invention should not be limited to the above exemplary embodiments.

[0089]

Explanation of symbols

[0090] 100: Manufacturing method

[0091] 110,120,122,124: steps.

Claims

1. A method for manufacturing an antibacterial anti-fog sheet, characterized in that: Include: A diionic polymer aqueous solution is provided, wherein the diionic polymer aqueous solution comprises a diionic polymer and water, and the diionic polymer comprises the copolymer described in Formula 1, R 1 is a thioether containing at least two acrylate groups; R 2 and R 3 is a hydrogen atom or a methyl group; R 4 are COOR' and CONR", and R' and R" are betaine, sulfobetaine or carboxybetaine; ionizing the dual-ion polymer aqueous solution using gas plasma to obtain a plasma-activated dual-ion polymer aqueous solution; and The sheet is immersed in the plasma activated double ion polymer aqueous solution to obtain the antibacterial anti-fog sheet.

2. The method for manufacturing the antibacterial anti-fog sheet according to claim 1, characterized in that: Before dipping the sheet in the plasma activated dual ion polymer aqueous solution, the sheet is subjected to plasma surface treatment.

3. The method for manufacturing the antibacterial anti-fog sheet according to claim 1, characterized in that: The sheet material comprises a substrate and at least two anti-reflection layers, and the substrate is disposed between the at least two anti-reflection layers.

4. The method for manufacturing the antibacterial anti-fog sheet according to claim 1, characterized in that: Wherein, based on the usage of the dual-ion polymer aqueous solution being 100 weight percent, the usage of the dual-ion polymer is 30 weight percent to 50 weight percent.

5. The method for manufacturing the antibacterial anti-fog sheet according to claim 1, characterized in that: The ionization treatment enables the dual-ion polymer to have at least one free radical.

6. The method for manufacturing the antibacterial anti-fog sheet according to claim 1, characterized in that: The antibacterial anti-fog sheet has at least one antibacterial anti-fog layer, and the thickness of the at least one antibacterial anti-fog layer is 0.5 μm to 50 μm.

7. The method for manufacturing the antibacterial anti-fog sheet according to claim 1, characterized in that: The ionization treatment is performed at 5° C. to 50° C. and 0.5 atmosphere to 1.5 atmosphere for 5 minutes to 120 minutes.

8. The method for manufacturing an antibacterial anti-fog sheet according to claim 1, characterized in that: The sheet is immersed in the plasma activated dual ion polymer aqueous solution for 5 minutes to 120 minutes.

9. An antibacterial anti-fog sheet, characterized in that: It is prepared by the manufacturing method according to any one of claims 1 to 8. 10.An antibacterial anti-fog glasses, characterized in that: The invention comprises the antibacterial anti-fog sheet according to claim 9.